Effect of Nitrogen Rate on Mucilage Content, Yield and Yield Components of Borage (Borago officinalis) - Eskandari, Bahareh; Razmjoo, Jamshid; Zahedi, Morteza (International Journal of Bio-resource and Stress Management, 2023)
Borage (Borago officinalis L. Boraginaceae) has been widely recognized as a medicinal plant with high nutritive value and for γ linolenic acid (GLA), extracted from the oil seed. Information on cultural practices for borage production is limited and evaluation of environmental factors affecting vegetative and seed yield would be required. In this study, the effect of 5 nitrogen levels including 0, 50, 100, 150 and 200 kg ha-1 on mucilage content, yield and yield components of borage was studied in a randomized complete block design with three replications. Nitrogen treatments had significant effect on the number of inflorescence per plant, the number of floret per plant, plant dry matter, flower and stem mucilage while plant height and leaf mucilage percentage were not affected by nitrogen treatment. The highest number of floret per plant as flower yield and mucilage of flower were found in 100 kg ha-1 nitrogen level. Using appropriate amount of nitrogen fertilizer is suggested to obtain higher mucilage for medicinal proposes in borage crop.